An Ultrarobust Composite Gel Electrolyte Stabilizing Ion Deposition for Long‐Life Lithium Metal Batteries. (25th August 2019) - Ding, Chenfeng; Fu, Xuewei; Li, Hao; Yang, Jiayi; Lan, Jin‐Le; Yu, Yunhua; Zhong, Wei‐Hong; Yang, Xiaoping
Abstract: Lithium metal batteries (LMBs) possessing ultrahigh energy density are promising next‐generation battery systems, but the short cycle life and safety concerns caused by the uncontrollable growth of lithium dendrites impede their broad applications. Herein, to address these issues, an ultrarobust composite gel electrolyte (CGE) that can effectively stabilize ion deposition for LMBs is designed via fabricating a specially structured aerogel as the matrix. The gel electrolyte matrix with a 3D interconnected highly porous structures and good affinity with liquid electrolytes is fabricated via compositing bacterial cellulose (BC) and Li0.33 La0.557 TiO3 nanowires (LLTO NWs) into an aerogel. The composite aerogel matrix demonstrates excellent wettability and liquid electrolyte uptake (586 ± 5%), and the resulting CGE presents exceptional Young's modulus of 1.15 GPa and an extremely high lithium‐ion transference number of 0.88. More significantly, the synergistic effect from the robust BC skeleton and LLTO NWs enabling stable ion deposition effectively suppresses the growth of lithium dendrites. Armed with the CGE, ultrastable symmetric Li/Li cells demonstrate a long cycle life of 1200 h and highly stable performance even at a high current density of 5 mA cm −2 . Furthermore, half cells with the CGE exhibit remarkable enhancement in capacity, cycling stability, and rate performance. Abstract : An ultrarobust composite gel electrolyte (CGE) simultaneously enabling stabilization of ion deposition and mechanical suppression of lithium dendrite growth is achieved. The resulting CGE presents high ionic conductivity, excellent Young's modulus, high lithium‐ion transference number, and good electrochemical/thermal stability. A strategy for design and fabrication of advanced ultrarobust gel electrolytes for fundamentally advanced lithium metal batteries is initiated.